The fat-burning bible : - Shilstone, Mackie (John Wiley & Sons, 2005)
This four-week plan is based on boosting the metabolic rate. Although Shilstone identifies various foods as being able to "burn fat," a misleading concept, still the diet, recipes, and exercise plans are reasonable and not dangerous in any way. The author of Lose Your Love Handles and Maximum Energy for Life, Shilstone has worked with heavyweight champions Michael Spinks and Roy Jones Jr. This guide, although it includes a diet for women, will appeal primarily to men